Stimulating Motivation of Low Class Students' Interest In Remote Regions Through Card Media and Image Media - Vino Putra Hadiyani; Haerul Salam (Sustainable, 2024)
This research is motivated by the existence of several low grade students who cannot read and there are still many students who cannot read fluently. Besides that, the motivation for students' interest in learning to read, the researchers saw that there was still a lack of motivation in reading. This was seen when in teaching reading, many students did it compulsorily, meaning that there was no motivation from themselves so that improving reading comprehension was not optimal. The purpose of this research and development is to produce a product in the form of word card media and picture cards to stimulate low grade students' motivation to read in remote areas. The method used in developing the product uses the ADDIE model. The results of product development research get a preset score of 93.39% with a very valid/feasible to use category. Product practicality results get a score percentage of 95.83%. The results of the research product developed in the form of word card media and picture card media to arouse motivation in low grade students' learning interest in remote areas of SDN Inpres Kala, Bima Regency are appropriate for use in learning because they have met the validity and practicality indicators of the validator